Reclamation Technology for Coal Post-Mining Land Contaminated by Acid Mine Drainage (AMD) (Jurnal Pengelolaan Lingkungan Pertambangan, 2025)
Indonesia, as a major coal producer and exporter, produced 775.2 million tons of coal in 2023, with mining activities concentrated in Kalimantan and Sumatera. Indonesia also holds 37.6 billion tons of coal reserves, ranking sixth globally. However, decades of coal extraction have led to severe environmental degradation, particularly through the formation of acid mine drainage (AMD). AMD is a highly acidic pollutant characterized by low pH and elevated concentrations of dissolved metals, formed when pyrite (FeS₂) and other sulfide minerals exposed during mining, oxidize upon contact with oxygen and water. This process significantly threatens water quality, soil health, and overall ecosystem integrity. To mitigate the environmental impacts of AMD, effective reclamation technologies are crucial. These include the application of ameliorants, the implementation of AMD management systems, and phytoremediation using hyperaccumulator plants. These methods aim to neutralize acidity, reduce metal concentrations, and restore ecosystem functions in coal post-mining land. The study applies a descriptive-analytical methodology to evaluate reclamation strategies implemented both in Indonesia and globally. The findings provide recommendations for effective and sustainable reclamation practices to mitigate AMD, rehabilitate degraded land, and ensure long-term environmental sustainability. Synthetic zeolite shows higher effectiveness in heavy metal adsorption, while natural zeolite is more cost-effective and sustainable. In managing AMD, the application of active and passive technologies combination should be adjusted to the specific characteristics of the site. Phytoremediation using hyperaccumulator plants has proven effective in reducing heavy metal contamination in both soil and water, by considering the type of contaminants and their absorption mediums